Between Scenarios: Traces of Customs in Tullio Victorino’s Paintings - Almeida, Elaine Karla de (Mimesis Journal, 2024)
This article provides a summary of the investigations about Portuguese painter Tullio Victorino. The research delves into the study of the artist’s life and inventories of his creative output—characters and scenarios portrayed throughout his artistic journey. Digital resources are employed to facilitate the recording and systematization of data, emphasizing the preservation and communication of this heritage to develop a digital collection about the artist’s life and work.